Evaluation of multiple water immersions of pathogen vector mosquito (Diptera: Culicidae) eggs - Dias, Rayane (2025)
Introduction: The hatching rate of mosquito eggs can vary according to their biological characteristics and environmental adaptations. Some species produce more resistant eggs, while others are more sensitive and require particular conditions to trigger hatching. Understanding how repeated contact with water influences the mosquito life cycle is critical for the integrated management of these vectors of etiological agents.Methods: Mosquito eggs were collected using 10 ovitraps placed in a forest remnant in the municipality of Uruaçu, state of Goiás, Brazil, during the rainy season in 2023. The egg-laden paddles were subjected to 27 weekly waterimmersion cycles in the laboratory.Results: Of the total eggs collected, 157 hatched and 136 reached the adult stage, representing four species. Aedes albopictus and Haemagogus leucocelaenus hatched after the first immersion, while Haemagogus janthinomys hatched between the 23rd and 25th immersions, and Aedes terrens hatched by the 26th immersion. The sex ratio of Ae. terrens showed a predominance of females (N = 72; 56.25%) over males (N = 56; 43.75%). Additionally, females required fewer immersion cycles to hatch compared to males.Discussion: The impact of multiple water immersions on egg hatching varied among species, particularly for Ae. terrens and Hg. janthinomys, which required a greater number of immersions to hatch. These results provide valuable insights into the mosquito biology and carry important implications for public health, given the role of these species as vectors of pathogens.